Analisis IMC Kopi Sheo: Pendekatan Aesthetic dan Kid-Friendly Tingkatkan Minat Beli Konsumen - Rachmadani, Nadia Puspita; Salas, Hagi Julio (CV. ITTC INDONESIA, 2025)
The development of modern marketing, influenced by advances in information technology and changes in consumer lifestyles, poses challenges for businesses, especially in the café industry. The problem addressed in this study is how the Integrated Marketing Communication (IMC) strategy implemented by Kopi Sheo Kotabumi can shape a strong and attractive brand image for consumers, particularly young people and families. This study aims to analyze the IMC strategy implemented by Kopi Sheo Kotabumi, which combines aesthetic and kid-friendly concepts to increase consumer purchasing interest. The method used is a qualitative descriptive approach with a case study, where data is collected through in-depth interviews and document analysis. Data analysis techniques were conducted in three stages: data reduction, data presentation, and conclusion drawing with triangulation of sources for data validation. The research results indicate that Kopi Sheo's IMC strategy successfully creates an appealing visual experience and a comfortable atmosphere for families, thereby increasing consumer loyalty and interest. Through the use of social media platforms like Instagram and TikTok, Kopi Sheo presents consistent and visually appealing content while conveying a message of inclusivity for families. This approach is reinforced by integrated public relations activities with the local community, as well as active and targeted internet marketing. This study confirms that the effective implementation of IMC can be a relevant strategy for micro-enterprises in non-metropolitan areas, focusing on aesthetics and family inclusivity values, thereby enhancing competitiveness and emotional customer engagement.